Method for efficiently preparing high-energy-density sodium-ion battery negative electrode material by one-step method

The one-step high-temperature annealing method is used to convert N,N-dimethyldithiocarbamate into a high-energy density carbon-based metal sulfide negative electrode material, which solves the problems of capacity, cycle stability and complex synthesis processes of existing sodium ion battery negative electrode materials, and achieves high energy density and good Coulomb efficiency.

CN119581502AInactive Publication Date: 2025-03-07LIAONING STARRY SKY SODIUM BATTERY CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411697813.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-03-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing sodium ion battery negative electrode materials have problems such as capacity, cycle stability and complex synthesis processes and difficult to repeat them stably, and the thermodynamics of the binding of graphite and other materials to sodium are unstable and difficult to apply.

Method used

By using one-step high-temperature annealing method, the iron N,N-dimethyldithiocarbamate was heated to 500-1300°C under a nitrogen atmosphere and cooled naturally for 2 hours to form a high-energy density carbon-based metal sulfide negative electrode material.

Benefits of technology

It achieves high energy density, good Coulomb efficiency and stability, simple operation steps, high repeatability, and the material is green and environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119581502A_ABST
    Figure CN119581502A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of sodium-ion battery negative electrode materials, and particularly discloses a method for efficiently preparing a high-energy-density sodium-ion battery negative electrode material by a one-step method, which comprises the following steps: heating iron N, N-dimethyl dithiocarbamate (thiram) to 500-1300 DEG C at a speed of 2-10 DEG C / min in a nitrogen atmosphere for 2 hours, and naturally cooling to room temperature to obtain the high-energy-density sodium-ion battery negative electrode material. The obtained black sample is the final material (FeS / NSC), and the steps are mainly divided into the following stages: stage 1: low temperature stage (500-700 DEG C); according to the invention, simple high-temperature annealing is carried out on the negative electrode material precursor to directly generate the sodium-ion battery negative electrode material with high energy density and high coulombic efficiency. The method has the advantages of being simple in operation step, high in repeatability, environmentally friendly and the like, and the finally obtained carbon-based metal sulfide negative electrode material has the specific capacity of 545 mAh / g and the first coulombic efficiency of 81% under the current density of 50 mA cm <-2 >.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of sodium ion battery negative electrode materials, and in particular to a one-step method for efficiently preparing a high-energy-density sodium ion battery negative electrode material. Background Art

[0002] The rapid economic development has led to the continuous improvement of people's material living standards, which has brought about huge consumption of electricity. my country's electricity supply is still mainly based on the combustion of fossil fuels. However, the non-renewable nature of fossil fuels determines the inevitability of the energy supply mode shifting to new renewable energy sources. However, the vigorous development of new energy conversion systems requires the simultaneous development of energy storage systems. In terms of energy storage systems, lithium-ion battery technology entered early and is relatively mature, but due to the scarcity of lithium resources in my country and the safety issues of lithium-ion batteries, its application in energy storage has been hindered. Therefore, it is necessary to develop a new energy storage system that is low-cost, highly safe, and green and environmentally friendly.

[0003] In terms of energy storage, sodium-ion batteries are considered to be complementary to lithium-ion batteries because of their similar working principles and low cost, high safety, and green environmental protection. Unlike lithium-ion battery negative electrodes, graphite cannot be used as a negative electrode material for sodium-ion batteries because the combination of sodium and graphite is thermodynamically unstable. Known negative electrode materials for sodium-ion batteries include alloy materials, hard carbon materials, organic compounds, and titanium-based materials, but they often face problems such as capacity, cycle stability, and complex synthesis processes that are difficult to repeat stably. Compared with the above materials, metal sulfide negative electrode materials have higher specific capacity, good conductivity, good cycle stability after being combined with carbon-based materials, and strong covalent bonding between metal ions and sulfur ions, which inhibits the stacking of metal sulfide layers in the Z-axis direction, thereby reducing the thickness of the material, shortening the migration distance of Na+, and promoting the conversion reaction.

[0004] N,N-dimethyldithiocarbamate iron (ferbam) is an agricultural fungicide. The loss of N, O, and S during pyrolysis allows it to be used as a self-etching template to generate a certain pore structure, and to generate a N, S-doped carbon-based and metal sulfide composite structure. This structure has high specific capacity, stability, and conductivity as a negative electrode material for sodium ion batteries. Therefore, we proposed a one-step method for efficiently preparing a negative electrode material for sodium ion batteries with high energy density. Summary of the invention

[0005] The purpose of the present invention is to solve the shortcomings of the prior art and to propose a one-step method and production process for efficiently preparing a negative electrode material for a sodium ion battery with high energy density.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] A one-step method for efficiently preparing a negative electrode material for a sodium ion battery with high energy density comprises the following steps: heating N,N-dimethyldithiocarbamate iron (ferbam) to 500-1300°C at 2-10°C / min under a nitrogen atmosphere for 2 hours, and naturally cooling to room temperature. The obtained black sample is the final material (FeS / NSC).

[0008] Preferably, the above steps are mainly divided into the following stages:

[0009] Stage 1: Low temperature stage (500-700℃): In this temperature range, N,N-dimethyldithiocarbamate iron begins to decompose. First, the sulfur-carbon (SC) bond and iron-sulfur (Fe-S) bond in the molecule will break, and the decomposition products include small sulfur-containing compounds, including dimethyl sulfide ((CH 3 )2 S ). An iron-containing sulfide intermediate is also produced, the structure and composition of which depends on how the iron and sulfur atoms recombine;

[0010] Stage 2: Medium temperature stage (700-1000℃): As the temperature rises further, the sulfide intermediates generated in the early stage will continue to decompose, and the iron-containing sulfide will undergo a desulfurization reaction to generate metallic iron particles and sulfur-containing gas. At high temperatures, the sulfur atoms in the sulfide will combine with the surrounding oxygen atoms to form sulfur dioxide and release it, while the iron atoms will aggregate to form metallic iron;

[0011] Stage 3: High temperature stage (1000-1300℃): In this high temperature range, the remaining organic components will be completely decomposed, and the carbon element will form carbides with iron. These reactions occur at extremely high temperatures. The chemical bonds of the molecules are subjected to strong thermal vibrations, resulting in the breaking of chemical bonds and the recombination of atoms, and ultimately forming various high-temperature decomposition products.

[0012] Stage 4: Changes during natural cooling: When the reaction is completed and the product is naturally cooled to room temperature, the gaseous products formed at high temperature will gradually condense or diffuse. For the solid products, metallic iron particles, iron carbide (Fe 3 C) and various iron sulfide compounds will undergo a crystal phase transition during the cooling process, from a high-temperature phase to a low-temperature stable phase. This process will make the crystal structure of the solid product more regular.

[0013] Preferably, in the first stage, the sulfur atom in N,N-dimethyldithiocarbamate iron is connected to the methyl group, and under the action of heat, these bonds break to release dimethyl sulfide ((CH 3 ) 2 S).

[0014] Preferably, in the second stage, the sulfur-containing gas includes sulfur dioxide.

[0015] Preferably, in the third stage, the dimethyl sulfide ((CH 3 ) 2 S) and small organic molecules will further decompose to produce methane (CH 4 ) and hydrogen (H 2 ), carbides include iron carbide (Fe 3 C).

[0016] Preferably, the dimethyl sulfide ((CH 3 ) 2 S), methane (CH 4 ) and hydrogen (H 2 ), as the temperature decreases, dimethyl sulfide will partially liquefy, while hydrogen and methane will remain in gaseous state and may diffuse into the surrounding environment or remain in gaseous state in a closed system, and the metallic iron particles will gradually transform from a disordered structure at high temperature to magnetic α-iron. This crystal phase transition will affect the physical and chemical properties of the material, including magnetic enhancement.

[0017] Compared with the prior art, the present invention has the following beneficial effects:

[0018] The present invention directly generates a sodium ion battery negative electrode material with high energy density and high coulombic efficiency by simply high-temperature annealing of the negative electrode material precursor. The method has the advantages of simple operation steps, high repeatability, and green environmental protection. The carbon-based metal sulfide negative electrode material finally obtained has a specific capacity of 545mAh / g and a first coulombic efficiency of 81% at a current density of 50mA cm-2. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 The first cycle charge and discharge curve of the FeS / NSC sodium ion battery composite material prepared by the present invention at a current density of 50mA cm-2;

[0020] Figure 2 The scanning electron microscope (SEM) image and energy dispersion distribution (EDS) image of different elements of the FeS / NSC sodium ion battery composite material prepared by the present invention are shown;

[0021] Figure 3 The X-ray diffraction pattern (XRD) of the FeS / NSC sodium ion battery composite material prepared in the present invention. DETAILED DESCRIPTION

[0022] The technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.

[0023] Please refer to 1- Figure 3 A one-step method for efficiently preparing a negative electrode material for a sodium ion battery with high energy density comprises the following steps: heating N,N-dimethyldithiocarbamate iron (ferbam) to 500-1300°C at 2-10°C / min under a nitrogen atmosphere for 2 hours, and then cooling naturally to room temperature. The obtained black sample is the final material (FeS / NSC).

[0024] As a technical optimization solution of the present invention, the above steps are mainly divided into the following stages:

[0025] Stage 1: Low temperature stage (500-700℃): In this temperature range, N,N-dimethyldithiocarbamate iron begins to decompose. First, the sulfur-carbon (SC) bond and iron-sulfur (Fe-S) bond in the molecule will break, and the decomposition products include small sulfur-containing compounds, including dimethyl sulfide ((CH 3 ) 2 S). Some iron-containing sulfide intermediates are also produced, the structure and composition of which depend on the way the iron atoms and sulfur atoms recombine;

[0026] Stage 2: Medium temperature stage (700-1000℃): As the temperature rises further, the sulfide intermediates generated in the early stage will continue to decompose, and the iron-containing sulfide will undergo a desulfurization reaction to generate metallic iron particles and sulfur-containing gas. At high temperatures, the sulfur atoms in the sulfide will combine with the surrounding oxygen atoms (from the structure of the compound itself or trace amounts of impurity oxygen) to form sulfur dioxide and release it, while the iron atoms will aggregate to form metallic iron;

[0027] Stage 3: High temperature stage (1000-1300℃): In this high temperature range, the remaining organic components will be completely decomposed, and the carbon element will form carbides with iron. These reactions occur at extremely high temperatures. The chemical bonds of the molecules are subjected to strong thermal vibrations, resulting in the breaking of chemical bonds and the recombination of atoms, and ultimately forming various high-temperature decomposition products.

[0028] Stage 4: Changes during natural cooling: When the reaction is completed and the product is naturally cooled to room temperature, the gaseous products formed at high temperature will gradually condense or diffuse. For the solid products, metallic iron particles, iron carbide (Fe 3 C) and various iron sulfide compounds will undergo a crystal phase transition during the cooling process, from a high-temperature phase to a low-temperature stable phase. This process will make the crystal structure of the solid product more regular.

[0029] As a technical optimization scheme of the present invention, in stage 1, the sulfur atom in N,N-dimethyldithiocarbamate iron is connected to the methyl group, and under the action of heat, these bonds break to release dimethyl sulfide ((CH 3 ) 2 S).

[0030] As a technical optimization solution of the present invention, in stage two, the sulfur-containing gas includes sulfur dioxide.

[0031] As a technical optimization solution of the present invention, in stage three, the dimethyl sulfide ((CH 3 ) 2 S) and small organic molecules will further decompose to produce methane (CH 4 ) and hydrogen (H 2 ) and other small molecule gases, carbides include iron carbide (Fe 3 C).

[0032] As a technical optimization solution of the present invention, in stage 4, dimethyl sulfide ((CH 3 ) 2 S), methane (CH 4 ) and hydrogen (H 2 ), etc. As the temperature decreases, dimethyl sulfide ((CH 3 ) 2 S) will partially liquefy (its boiling point is 37.5°C), while hydrogen (H 2 ) and methane (CH 4 ) etc. are still in gaseous state and may diffuse into the surrounding environment (if the system is open) or remain in gaseous state in a closed system. The metallic iron particles will gradually transform from the disordered structure at high temperature to magnetic α-iron (body-centered cubic structure). This crystal phase transition will affect the physical and chemical properties of the material, including magnetic enhancement.

[0033] When the present invention is used, Figure 1 It can be clearly seen that the first cycle discharge and charge can reach 671mAhg-1 and 545mAh g-1 respectively, and the first coulombic efficiency is 81%, indicating that the prepared FeS / NSC has a high specific capacity and first coulombic efficiency; Figure 2 , where ac are the material morphologies at different magnifications, mainly showing uniform granularity. Figure 2 d analyzed the elements and distribution in the material. It can be clearly seen that S, Fe, O, C, and N are evenly distributed in the particles without obvious team formation, indicating that the components in the material prepared by the invention are very uniform. Figure 3, it can be seen that the diffraction peak of FeS / NSC corresponds to FeS (JCPDF 04-004-6646), indicating the successful synthesis of metal sulfide FeS in the prepared material. FeS plays a vital role in improving the overall specific capacity of the material. The distribution of carbon in the above EDS proves the composite of the material and carbon, which improves the stability of the material.

[0034] The above are only preferred specific implementation modes of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical solutions and inventive concepts of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A one-step method for efficiently preparing a negative electrode material for a high energy density sodium ion battery, characterized in that: The method comprises the following steps: heating N,N-dimethyldithiocarbamate iron (ferbam) to 500-1300°C at 2-10°C / min under a nitrogen atmosphere for 2 hours, and naturally cooling to room temperature. The obtained black sample is the final material (FeS / NSC).

2. The method for efficiently preparing a negative electrode material for a sodium ion battery with high energy density in one step according to claim 1, characterized in that: The above steps are mainly divided into the following stages: Stage 1: Low temperature stage (500-700℃): In this temperature range, N,N-dimethyldithiocarbamate iron begins to decompose. First, the sulfur-carbon (SC) bond and iron-sulfur (Fe-S) bond in the molecule will break, and its decomposition products include small sulfur-containing compounds, including dimethyl sulfide ((CH3)2S). Iron-containing sulfide intermediates are also generated, and their structure and composition depend on the recombination of iron atoms and sulfur atoms; Stage 2: Medium temperature stage (700-1000℃): As the temperature rises further, the sulfide intermediates generated in the early stage will continue to decompose, and the iron-containing sulfide will undergo a desulfurization reaction to generate metallic iron particles and sulfur-containing gas. At high temperatures, the sulfur atoms in the sulfide will combine with the surrounding oxygen atoms to form sulfur dioxide and release it, while the iron atoms will aggregate to form metallic iron; Stage 3: High temperature stage (1000-1300℃): In this high temperature range, the remaining organic components will be completely decomposed, and the carbon element will form carbides with iron. These reactions occur at extremely high temperatures. The chemical bonds of the molecules are subjected to strong thermal vibrations, resulting in the breaking of chemical bonds and the recombination of atoms, and ultimately forming various high-temperature decomposition products. Stage 4: Changes during natural cooling: When the reaction is completed and the product is naturally cooled to room temperature, the gaseous products formed at high temperature will gradually condense or diffuse. For the solid products, metallic iron particles, iron carbide (Fe3C) and various iron sulfide compounds, a crystal phase transition will occur during the cooling process, from a high-temperature phase to a low-temperature stable phase. This process will make the crystal structure of the solid product more regular.

3. The method for efficiently preparing a negative electrode material for a sodium ion battery with a high energy density in one step according to claim 2, characterized in that: In the first stage, the sulfur atoms in N,N-dimethyldithiocarbamate iron are connected to methyl groups, and under the action of heat, these bonds break to release dimethyl sulfide ((CH3)2S).

4. The method for efficiently preparing a negative electrode material for a sodium ion battery with high energy density in one step according to claim 2, characterized in that: In the second stage, the sulfur-containing gas includes sulfur dioxide.

5. The method for efficiently preparing a negative electrode material for a sodium ion battery with high energy density in one step according to claim 2, characterized in that: In the third stage, dimethyl sulfide ((CH3)2S) and small molecule organic compounds generated in the first stage are further cracked to generate methane (CH4) and hydrogen (H2), and carbides include iron carbide (Fe3C).

6. The method for efficiently preparing a negative electrode material for a sodium ion battery with high energy density in one step according to claim 2, characterized in that: In the fourth stage, dimethyl sulfide ((CH3)2S), methane (CH4) and hydrogen (H2) are gaseous at high temperatures. As the temperature decreases, dimethyl sulfide ((CH3)2S) will partially liquefy, while hydrogen (H2) and methane (CH4) will remain in gaseous form and may diffuse into the surrounding environment or remain in gaseous form in a closed system. The metallic iron particles will gradually transform from a disordered structure at high temperatures into α-iron with magnetic properties. This crystal phase transition will affect the physical and chemical properties of the material, including magnetic enhancement.

Citation Information

Patent Citations

  • Method for preparing general nano metal sulphide

    CN101857276A

  • Positive electrode material for zinc-nickel single-liquid flow battery and preparation and application thereof

    CN109786767A

  • Method for preparing sodium ion battery by using porous carbon and carbon nanotube composite material generated from rice hulls

    CN118270784A

  • Positive-electrode active material for lithium-ion secondary battery, positive electrode and lithium-ion secondary battery

    US20170288225A1